2015
DOI: 10.1521/pedi_2014_28_164
|View full text |Cite
|
Sign up to set email alerts
|

Adaptive and Maladaptive Personality Traits in High-Risk Gamblers

Abstract: Gambling Disorder (GD) is an addictive disorder resulting in significant impairment in occupational and social functioning. The aim of the present study was to investigate the relationship of GD risk to adaptive and maladaptive personality dimensions in a sample of nonreferred Italian gamblers. The authors found the risk for GD to show significant associations with the Openness and Conscientiousness scales of the Big Five Inventory (BFI); however, these effects were not significant after controlling for alcoho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
15
3
1

Year Published

2016
2016
2019
2019

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 33 publications
(23 citation statements)
references
References 52 publications
4
15
3
1
Order By: Relevance
“…Also, this converges with the study of Nigro et al (2018) conducted in a non-clinical population of gamblers and showing a positive association between all the five domains of the PID-5 Short-Form and GD's severity. However, our findings partially disagree with the study of Carlotta et al (2015) which reported significant differences between high-risk and low-risk gamblers only on the Detachment and Antagonism domains. This discrepancy may be explained by the differences in the measure of GD of Carlotta et al's studya two item instrument investigating lying-behaviors related to gamblingpotentially leading to an over-representation of antisocial features among high-risk gamblers.…”
Section: Discussioncontrasting
confidence: 99%
See 3 more Smart Citations
“…Also, this converges with the study of Nigro et al (2018) conducted in a non-clinical population of gamblers and showing a positive association between all the five domains of the PID-5 Short-Form and GD's severity. However, our findings partially disagree with the study of Carlotta et al (2015) which reported significant differences between high-risk and low-risk gamblers only on the Detachment and Antagonism domains. This discrepancy may be explained by the differences in the measure of GD of Carlotta et al's studya two item instrument investigating lying-behaviors related to gamblingpotentially leading to an over-representation of antisocial features among high-risk gamblers.…”
Section: Discussioncontrasting
confidence: 99%
“…The association found in our study between this facet and GD's severity agrees with the conclusion drawn by Carlotta et al . () supporting the asserted association between Antisociality and GD (Rogier, Velotti & Zavattini, ).…”
Section: Discussionsupporting
confidence: 93%
See 2 more Smart Citations
“…Openness may be a burden as well -e.g. in the case when you have to do an ordinary, boring job; it also seems to be a risk factor of gambling disorder (Carlotta et al, 2015). Extraversion -a trait that includes positive emotionality (McCrae & Costa, 1987) -should also be treated with caution, as it is not introversion which predicts negative emotionality, but neuroticism (i.e.…”
Section: Introductionmentioning
confidence: 99%